OVERWEIGHT AND OBESITY PREVALENCE IN SCHOOL STUDENTS OF PERNAMBUCO`S COUNTRYSIDE, BRASIL. (Fiep Bulletin - online, 2011)
The objective of this present study was to describe the overweight and obesity prevalence in students of a public school from Alagoinha, Pernambuco. The sample was composed by children and teenagers with age ranging from 10 to 11 and 12 to 17 years old, respectively. They were middle school students from 6th to 9th grade, in a total of 256 students, where 142 were females and 114 were males. Their height and body mass were measured to acquire their body mass index (BMI). We considered children and teenagers with BMI lower than 5% for their age with low weight; BMI higher or equal to 85% and lower than 95% for their age were overweight; BMI equal or higher to 95% for their age were considered obese. The data analysis was made through the qui-square proportion  or Ficher test. The significance level established was p< 0,05. The results showed that in relation to overweight, 9,7% of the individuals were in this category, occuring with higher frequency between the girls (12%). In relation to obesity, 3,9% of the sample was considered obese (n=10), which 6,9% (n=8) were boys and 1,4% (n=2) were girls. Concerning the age range, we observed that the overweight was more frequent among teenagers between 12 and 13 years old (10.8%). For obesity, the values were more relevant for children (5,7%). In sumary, we conclude that the overweight was more prevalent among the boys than among the girls.
Keywords: Obesity; Overweight; Teenagers; Children